::OMPARATIVE STUDIES ON THE CANNING PROPERTIES OF POMFRETS AND HILSA - VENKATARAMAN, R; KANDORAN, M K; RAJE, C R (Fishery Technology, 2025)
Fresh silver pomfret, black pomfret and hilsa were canned at absolutely fresh and iced conditions and the qualities of the final products were studied comparatively in relation to th initial quality of the raw materials. Under identical conditions a maximum quantity of cook-drip and nitrogen contents were found to be lost in black pomfret and minimum in hiJsa. Silver pomfret and black pomfret iced for 3 days gave fairly good products on canning while hilsa came out only as a satisfactory product on canning after the same ice storage period of the raw material.